Clinical Pain-related Outcomes and Inflammatory Cytokine Response to Pain Following Insomnia Improvement in Adults With Knee Osteoarthritis. Issue 12 (December 2018) - Heffner, Kathi L.; France, Christopher R.; Ashrafioun, Lisham; Quiñones, Maria; Walsh, Patrick; Maloney, Michael D.; Giordano, Brian D.; Pigeon, Wilfred R.
Abstract : Objectives: Clinical insomnia is known to affect pain, but mechanisms are unclear. Insomnia can dysregulate inflammatory pathway, and inflammation plays a mediating role in pain. It is unclear whether insomnia-related alterations in inflammation can be modified with insomnia improvement, and if such alterations parallel improvement in pain. The current study objective was to provide proof of concept for the role of insomnia in inflammation and pain by testing whether improving insomnia would reduce pain and related physical function, and, concurrently, modulate inflammatory responses. Materials and Methods: Thirty adults with osteoarthritis knee pain and insomnia (Insomnia Severity Index >10) provided baseline measures of osteoarthritis and laboratory pain, and serial blood samples for inflammatory biomarkers, interleukin 6, and tumor necrosis factor α, before and after pain testing. To manipulate insomnia, participants were randomly assigned to a 6-week cognitive-behavioral therapy for insomnia (n=16); or wait-list control (n=14). At 8-weeks (time 2), all measures were repeated. To directly test insomnia improvement effects, participants were grouped by insomnia status at time 2 after confirming baseline equivalency on all outcomes. Results: Compared with those maintaining insomnia at time 2 (Insomnia Severity Index ≥8; n=18), those whose insomnia improved at time 2 (n=12) had significantly improved physical functioning, decline in knee pain during transfer activities, and attenuated increase in interleukin 6 and less decrease in tumor necrosis factor α across the pain testing session. Discussion: These findings suggest further exploration of inflammatory pathways linking clinical insomnia, and its improvement, to chronic pain.